PETIS: Pendampingan Intensif untuk Anak Sehat dalam Mengatasi Masalah Stunting di Kelurahan Tukmudal, Cirebon - Aries, Muhammad; Pamungkas, Pandu; Agung, Sangaji Permono; Nusaibah, Nusaibah; Banupa, Zoraya Nurafifa; Alsyah, Aurelia Vania; Iskandar, Allamah Shabrina; Wahyuni, Silvia Sry; Muhammad, Mirza Hafiz; Ramadhina, Rakanita Faatihah (Jurnal Pusat Inovasi Masyarakat, 2024)
Stunting represents a chronic nutritional problem that persists at a high prevalence (8%) in Cirebon. Intensive Mentoring Program for Healthy Children (PETIS) was implemented in Tukmudal, Cirebon, with the objective of addressing the issue of stunting. This program involves five stunted children selected by accident from two Posyandu with the highest prevalence of stunting. The methodology employed encompassed a range of techniques, including anthropometric measurements, 24-hour recall interviews to assess children's feeding practices, nutrition education, and supplementary feeding. Nutritional education was conducted in stages over a period of three weeks, with different topics addressed each week. These included balanced nutrition patterns, motor development, and clean and healthy living behavior (PHBS). The results of this programme demonstrate that intensive nutrition education can enhance mothers' awareness of the importance of a balanced diet and clean living behavior in stunting prevention. Furthermore, the mentoring programme succeeded in encouraging the growth of children's BW and PB/TB. However, dietary modifications among children remain constrained. Therefore, a more comprehensive and sustainable strategy is essential to achieve optimal nutritional advancement.